Determinants of Stock Returns in Food and Beverage SubSector Manufacturing Companies - Edisah Putra Nainggolan; Firya Naziha Parinduri (International Journal Of Economics Social And Technology, 2022)
This study aims to determine the effect of Return On Assets on stock returns in food and beverage companies on the Indonesia Stock Exchange. To determine the effect of Return On Equity on stock returns in food and beverage companies on the Indonesia Stock Exchange. in food and beverage companies on the Indonesia Stock Exchange. This research approach uses a quantitative associative approach. The population used in this study is a financial report. The total population of food and beverage companies is 51 and the sample is 11 food and beverage companies listed on the IDX. Analysis of the data used in this study is quantitative data using classical assumption test, multiple regression, and hypothesis testing. Based on the results of the study there is a significant effect of ROA on stock returns in food and beverage companies listed on the IDX. There is a significant effect of ROE on stock returns in food and beverage companies listed on the IDX. There is a significant effect of NPM on stock returns in food and beverage companies listed on the IDX. There is a significant effect of ROA, ROE, and NPM on stock returns in food and beverage companies listed on the BEI